The relevance of personal characteristics and gender diversity for (eco)-innovation activities at the firm-level: Results from a linked employer-employee database in Germany - Jens Horbach; Jojo Jacob (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
Up to now, the growing literature on the determinants of eco-innovation has not considered the influence of personal characteristics of the employees of a firm. The existing econometric analyses show much "noise" explaining the driving forces of ecoinnovation. The paper tries to open the "black box" of unexplained heterogeneity. In fact, latent variables such as the greenness of a firm may be explained by the personal characteristics (gender, family status, geographical origin, education etc.) of the staff and the decision makers in a firm. The linked employer-employee database of the Institute for Employment Research (IAB) in Germany allows such an analysis based on data for 2010 and 2012. The results of an econometric analysis show that a high share of high qualified women and a mixed gender composition of the management board are positively correlated to eco-innovation activities. Furthermore, the results confirm that export-oriented firms are more likely to innovate, firms characterized by an over-aging of the staff innovate less and a higher competition pressure leads to more innovations. – – In der mittlerweile umfangreichen Literatur zu den Determinanten von Umweltinnovationen wurde bislang die Rolle persönlicher Charakteristika der Beschäftigten der Unternehmen noch nicht berücksichtigt. Ökonometrische Analysen zu Umweltinnovationen weisen häufig einen hohen Anteil unerklärter Streuung auf, was auch auf die fehlende Berücksichtigung personenbezogener Variablen zurückgeführt werden könnte. So lassen sich u.U. latente Variablen wie die "grüne" Ausrichtung eines Unternehmens zumindest teilweise durch persönliche Charakteristika (Geschlecht, Familienstatus, geografische Herkunft, Ausbildungsstand) der Belegschaft und des Managements erklären. Der linked employer-employee Datensatz des Instituts für Arbeitsmarkt- und Berufsforschung erlaubt eine solche Untersuchung für 2010 bzw. 2012. Die Ergebnisse einer ökonometrischen Analyse zeigen, dass ein hoher Anteil hochqualifizierter Frauen in der Belegschaft und eine geschlechtergemischte Zusammensetzung des Managements die Durchführung von Umweltinnovationen begünstigen. Darüber hinaus bestätigen die Ergebnisse, dass exportorientierte Betriebe sowie Betriebe, die einem hohen Wettbewerbsdruck unterliegen, mehr Innovationen realisieren, während das Gegenteil für Betriebe mit überalterter Belegschaft gilt
Keywords: C35; J16; Q55; 330; Eco-innovation; probit model; linked employer-employee data